2022
DOI: 10.3390/jpm12122045
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Role of Systemic Inflammatory Markers in the Development of Acute Kidney Failure and Mortality in Patients with Abdominal Trauma

Abstract: Background: Abdominal trauma is defined as a variety of injuries to the abdominal wall, solid or hollow intra-abdominal organs, and various intra-abdominal vessels. Recently, there has been a significant amount of interest in the establishment of a reliable biomarker that can predict the outcome in patients with an abdominal injury. The purpose of this study is to confirm the predictive role of inflammatory biomarkers and underlying risk factors and the risk of acute kidney insufficiency (AKI) developing and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…Regarding the laboratory parameters, we included in this study the laboratory data from samples taken pre-operatively. In terms of systemic inflammatory markers, we measured the IL-6 level and hematological ratios (neutrophil–lymphocyte ratios (NLR), platelet–lymphocyte ratios (PLR), and the systemic inflammatory index (SII)) [ 3 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The patients provided written informed consent for the publication of any data.…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the laboratory parameters, we included in this study the laboratory data from samples taken pre-operatively. In terms of systemic inflammatory markers, we measured the IL-6 level and hematological ratios (neutrophil–lymphocyte ratios (NLR), platelet–lymphocyte ratios (PLR), and the systemic inflammatory index (SII)) [ 3 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. The patients provided written informed consent for the publication of any data.…”
Section: Methodsmentioning
confidence: 99%
“…Vulvulea et al 20 . discovered that NLR, PLR, and SII values played a significant predictive role in the development of acute kidney insufficiency (AKI) and mortality risk in patients with abdominal trauma.…”
Section: Discussionmentioning
confidence: 99%
“…The receiver operating characteristics analysis of the neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, and systemic immune inflammation index in predicting therapeutic surgery. [Colour figure can be viewed at wileyonlinelibrary.com] Vulvulea et al 20 discovered that NLR, PLR, and SII values played a significant predictive role in the development of acute kidney insufficiency (AKI) and mortality risk in patients with abdominal trauma. Yucel et al 5 found that leukocytes, leukocyte subgroups, NLR and PLR were significantly effective in determining the necessity of laparotomy in 547 patients with ASW who lacked immediate surgical findings.…”
Section: F I G U R Ementioning
confidence: 99%
“…SIRI was initially used for the assessment of tumor prognosis (31,32), however, the latest findings suggest that an elevated SIRI strongly correlates with unfavorable outcomes in acute coronary syndrome, cardiovascular event mortality, arrhythmias among stroke patients, and major adverse cardiovascular events following percutaneous coronary intervention (PCI) (33)(34)(35). A limited number of studies suggest that SIRI may offer distinct predictive utility in the prediction of acute kidney injury resulting from abdominal trauma (36). An analysis of SIRI elevation and cardiovascular mortality risk in hypertensive patients revealed that those in the fourth quartile of SIRI had a 2.9-fold increased risk of cardiovascular death compared to patients in the first quartile (37).…”
Section: Introductionmentioning
confidence: 99%